2018
DOI: 10.1371/journal.pone.0193955
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic motivators of attachment under active inference

Abstract: This paper addresses the formation of infant attachment types within the context of active inference: a holistic account of action, perception and learning in the brain. We show how the organised forms of attachment (secure, avoidant and ambivalent) might arise in (Bayesian) infants. Specifically, we show that these distinct forms of attachment emerge from a minimisation of free energy—over interoceptive states relating to internal stress levels—when seeking proximity to caregivers who have a varying impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 88 publications
1
10
0
Order By: Relevance
“…This is in line with research which has shown that affective communication errors are associated with both ambivalent and disorganized attachment patterns (Bronfman et al, 1999 ; Safyer, 2013 ). The observation that these models produce responses that are in line with what is expected from previous theory and research on attachment, is offered as strong support for a FEP based computational model of the child's responses to a caregiver (Cittern et al, 2018 ). With regard to the formulation being offered in this paper, this work supports the grounding of a process of conflict within a FEP-based model, that may be organized by interactional process as suggested by Hopkins ( 2016 ).…”
Section: Conflict In the Strange Situationsupporting
confidence: 66%
See 1 more Smart Citation
“…This is in line with research which has shown that affective communication errors are associated with both ambivalent and disorganized attachment patterns (Bronfman et al, 1999 ; Safyer, 2013 ). The observation that these models produce responses that are in line with what is expected from previous theory and research on attachment, is offered as strong support for a FEP based computational model of the child's responses to a caregiver (Cittern et al, 2018 ). With regard to the formulation being offered in this paper, this work supports the grounding of a process of conflict within a FEP-based model, that may be organized by interactional process as suggested by Hopkins ( 2016 ).…”
Section: Conflict In the Strange Situationsupporting
confidence: 66%
“…A detailed computational model of the interaction between caregiver and child that simulates the emergence of an attachment pattern in the child has recently been published by Cittern et al ( 2018 ). In their model a Bayesian approach based on active inference (based on the FEP) is deployed within a game theoretical framework where a child agent has three available actions, “seek,” “guarded seek,” or “avoid.” In return, a caregiving agent may be “highly responsive,” “inconsistently responsive,” and consistently “unresponsive,” expressed in terms of “attend” or “ignore” behavior.…”
Section: Conflict In the Strange Situationmentioning
confidence: 99%
“… 8 For a recent example of a simulated infant learning about mother’s quality of caregiving under active inference, see Cittern et al (2018).…”
mentioning
confidence: 99%
“…Furthermore, there is evidence of intergenerational effects of ACEs and trauma through links between parental ACE scores and child exposure to ACEs, coined as "secondary trauma" by Mersky et al (2013). These effects of ACEs can be displayed through intergenerational transitions of attachment types, as parent-child interactions and parental mental health are a large determinant of a child's attachment style (Cittern et al, 2018). If a child is to transition from a secure to insecure attachment style, it is often linked to higher ACE scores or traumatic experiences of either the parent or the child (Cittern et al, 2018).…”
Section: Consequences Of Aces In Child Development and Lifelong Healthmentioning
confidence: 99%
“…Childhood experiences, both positive and negative, shape the physical, mental, and social health of individuals throughout their entire lives. Early childhood adversity and its residual effects of toxic stress are shown to impact both early development and long-term health outcomes well into adulthood (Cittern et al, 2018;Espeleta et al, 2018;Flores & Salazar, 2017;Grey et al, 2019;McKelvey et al, 2019;Mersky et al, 2013;National Scientific Council on the Developing Child, 2020). The purpose of this literature review is to synthesize existing literature to analyze the influences of Adverse Childhood Experiences (ACEs), including the COVID-19 pandemic context as an ACE, and toxic stress on child development and lifelong health outcomes of Latinx children in the USA and its adverse impacts on Latinx communities.…”
Section: Introductionmentioning
confidence: 99%